2012
DOI: 10.1002/jmr.2207
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a mannose/N‐acetyl‐ d‐glucosamine‐specific lectin from the seeds of Platymiscium floribundum Vogel

Abstract: Platymiscium floribundum lectin (PFL), a mannose/N-acetyl-D-glucosamine-specific lectin, was isolated from P. floribundum seeds using Sepharose-mannose affinity media chromatography. PFL is a glycoprotein that is a potent agglutinin for rabbit erythrocytes. In addition, PFL is highly stable because it is able to maintain its hemagglutinating activity after exposure to temperatures of up to 60 °C for 1 h and exposure to a wide pH range. The PFL purification process was monitored using sodium dodecyl sulfate-pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
3
10
1
1
Order By: Relevance
“…The results are shown in Table 2. Similar results were reported for lectins from Platymiscium floribundum [16], Centrolobium microchaete [18] and Canavalia virosa [37]. Lis and Sharon [38] revealed that trypsin can be used to modify the erythrocytes surface to enhance its affinity for lectins without affecting the total number of lectin binding sites on the erythrocytes.…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…The results are shown in Table 2. Similar results were reported for lectins from Platymiscium floribundum [16], Centrolobium microchaete [18] and Canavalia virosa [37]. Lis and Sharon [38] revealed that trypsin can be used to modify the erythrocytes surface to enhance its affinity for lectins without affecting the total number of lectin binding sites on the erythrocytes.…”
Section: Resultssupporting
confidence: 77%
“…The loss of activity of the lectin with increased temperature is due to destabilization of sporadic weak interactions of tertiary structure responsible for native conformation of lectin [39]. These results are comparable to the reported results of lectins purified from Vatairea marcocarpa [11], Vatairea guianensis [15], Platymiscium floribundum [16], and Canavalia oxyphylla [42]. In contrast, extremely thermostable lectins have been reported from Bauhinia forficate [43] and Apuleia leiocarpa [44].…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations